37 Emergency medical dispatchers' perception of barriers in handling emergency calls. a qualitative study. (21st May 2017) - Møller, TP; Jensen, H Gamst; Viereck, S; Lippert, FK; Østergaard, D
Abstract : Aim: Medical dispatching is a highly complex procedure and has an impact upon patient outcome. It includes handling emergency calls, prioritisation of resources and the provision of guidance and instructions to callers. Whilst emergency medical dispatchers play a key role in the process, their perception of the process is rarely reported. We explored emergency medical dispatchers' perception of their role in emergency call handling and their perception of barriers. Methods: An explorative qualitative interview study was designed. Modified grounded theory was used for the data analysis. Results: A total of 5 paramedics and 6 registered nurses were interviewed. A model of the emergency call handling process was drawn based on the data. The analysis of barriers resulted in themes relating to the callers and the medical dispatchers, from whom four and three respective themes were identified. For callers, the motive for calling, the situation, the perception and presentation of the problem was influencing factors. For the dispatchers the expertise, teamwork and organisation influenced the process. Conclusion: The results indicate factors influencing the medical dispatch process, as perceived by medical dispatchers. Callers lack knowledge about best utilisation of the emergency number and the medical dispatching process, which can be improved by public awareness campaigns and incorporation of knowledge in first aid courses. For medical dispatchers the most potent modifiable factors were based upon the continuous professional development of the medical dispatchers and the system that supports them. Conflict of interest: None declared. Funding: EMS, Copenhagen receives centre support from the Laerdal Foundation for Acute Medicine.